Enantioseparation of Citalopram by RP-HPLC, Using Sulfobutyl Ether-β-Cyclodextrin as a Chiral Mobile Phase Additive. (5th January 2016) - Peng, Yangfeng; He, Quan Sophia; Cai, Jiang
Abstract : Enantiomeric separation of citalopram (CIT) was developed using a reversed phase HPLC (RP-HPLC) with sulfobutylether- β -cyclodextrin (SBE- β -CD) as a chiral mobile phase additive. The effects of the pH value of aqueous buffer, concentration of chiral additive, composition of mobile phase, and column temperature on the enantioseparation of CIT were investigated on the Hedera ODS-2 C18 column (250 mm × 4.6 mm × 5.0 um). A satisfactory resolution was achieved at 25°C using a mobile phase consisting of a mixture of aqueous buffer (pH of 2.5, 5 mM sodium dihydrogen phosphate, and 12 mM SBE- β -CD), methanol, and acetonitrile with a volumetric ratio of 21 : 3 : 1 and flow rate of 1.0 mL/min. This analytical method was evaluated by examining the precision (lower than 3.0%), linearity (regression coefficients close to 1), limit of detection (0.070 µ g/mL for (R )-CIT and 0.076 µ g/mL for (S )-CIT), and limit of quantitation (0.235 µ g/mL for (R )-CIT and 0.254 µ g/mL for (S )-CIT).